Stochastic Process Costing Models. - Corcoran, A. Wayne; Leininger, Wayne E. (The Accounting Review, 1973)
Abstract The article presents information on the development of stochastic process costing models in accounting. In a deterministic production system, all units would pass in a common sequence through the processes and exit the system as final product. However, many mass production systems cannot be classified as deterministic. The process costing models developed in this article are based on the premise that product flows within a mass production system can be described stochastically. Time is handled in two ways resulting in two models. Standard costs is integrated into the models for the purpose of costing output and inventories. The costing phase of the model has only been designed for a single entry system. In a multiple entry system, different transfer and output costs would be required for each entry point. Output and inventories would be coasted based on the expected entry point. The possibility of non-sequential transfers is another condition that would complicate the allocation of costs. Non-sequential transfers will be considered in a later section of this paper.